Benefits of early antifungal therapy in hematology patients - S. S. Andreev; G. O. Bronin; N. Yu. Epifanova; O. P. Kozlova; E. A. Pristanskova; S. N. Khostelidi; O. V. Shadrivova (Онкогематология, 2024)
Invasive fungal infections (IFIs) are a serious threat to patients with hematological diseases. These infections are characterized by high mortality and lead to significant financial costs for treatment. The most common pathogens of IFIs are Aspergillus spp. and Candida spp., but in recent years, cases of infections caused by rare pathogens have become more frequent. Diagnosis of IFIs and choice of treatment remain challenging due to the nonspecificity of symptoms and the diversity of clinical cases. In this regard, the problem of start time and choice of antifungal therapy remains of current interest. This review briefly describes diagnostic criteria, challenges associated with IFIs diagnosing, provides evidence for empiric and preventive strategies as two early treatment approaches, and examines the impact of therapy initiation on patient outcomes. Treatment of IFIs in hematologic patients should be individualized. At the same time, early administration of therapy with broad-spectrum drugs for febrile neutropenia and parallel diagnostic measures can improve treatment outcomes. There is a lack of current data on the benefits of specific treatment strategies, highlighting the need for further research.